(untitled) (Palestine Technical College Journal for Research and Studies, 2023)
The study aimed to identify the extent to which infographic art is used by Palestinian partisan newspapers, the motives behind its use, the gratifications achieved through its use, as well as its advantages and disadvantages. To achieve the objectives of the study, the researchers employed the survey method and adopted a comprehensive survey approach. The study population and sample consisted of (30) employees working at Al-Resalah and Al-Istiqlal newspapers. The study yielded several findings, most notably the ease of using infographic art in realistic visual representation and the ability of some Palestinian newspapers to employ it effectively. The findings also indicated that designing infographics requires the ability and skill to represent data visually. Furthermore, the results revealed statistically significant differences in the use of infographic art by partisan newspapers in the Gaza Strip attributable to the profession variable, whereas no statistically significant differences were found with respect to gender, age, or newspaper affiliation. The study recommended expanding the use of infographic art in partisan newspapers, introducing modern technological tools and techniques into the journalistic work environment, and increasing training programs for newspaper staff on the effective use of infographics, thereby enhancing their application and further developing their use in partisan newspapers.